Integration of Traditional Birth Attendants into Prevention of Mother-to-Child Transmission at Primary Health Facilities in Kaduna, North-West Nigeria - Nsirim, Reward O. (J Public Health Africa, 2015)
One of the fundamental challenges to implementing successful prevention of mother-to-child transmission (PMTCT) programs in Nigeria is the uptake of PMTCT services at health facilities. Several issues usually discourage many pregnant women from receiving antenatal care services at designated health facilities within their communities. The CRS Nigeria PMTCT Project funded by the Global Fund in its Round 9 Phase 1 in Nigeria, sought to increase demand for HIV counseling and testing services for pregnant women at 25 supported primary health centers (PHCs) in Kaduna State, North-West Nigeria by integrating traditional birth attendants (TBAs) across the communities where the PHCs were located into the project. Community dialogues were held with the TBAs, community leaders and women groups. These dialogues focused on modes of mother to child transmission of HIV and the need for TBAs to refer their clients to PHCs for testing. Subsequently, data on number of pregnant women who were counseled, tested and received results was collected on a monthly basis from the 25 facilities using the national HIV/AIDS tools. Prior to this integration, the average number of pregnant women that were counseled, tested and received results was 200 pregnant women across all the 25 health facilities monthly. After the integration of TBAs into the program, the number of pregnant women that were counseled, tested and received results kept increasing month after month up to an average of 1500 pregnant women per month across the 25 health facilities. TBAs can thus play a key role in improving service uptake and utilization for pregnant women at primary health centers in the community – especially in the context of HIV/AIDS. They thus need to be integrated, rather than alienated, from primary healthcare service delivery.